2003
DOI: 10.1523/jneurosci.23-07-03076.2003
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Responsiveness to Novelty and Cocaine Is Associated with Decreased Basal Dopamine Uptake and Release in the Nucleus Accumbens: Quantitative Microdialysis in Rats under Transient Conditions

Abstract: Male rats were screened for their response to a novel environment and designated as high responders (HRs) or low responders (LRs). They then received daily injections of saline or cocaine (20 mg/kg, i.p.). Basal and cocaine-evoked extracellular dopamine (DA(ext)) levels as well as basal DA uptake rate and cocaine-evoked inhibition of uptake in the nucleus accumbens were determined on abstinence day 3 using quantitative microdialysis under transient conditions. The kinetics of uptake, dopamine transporter (DAT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
3
6

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 31 publications
4
70
3
6
Order By: Relevance
“…In particular, HR-LR differences in cocaine's impact on the FADD system may emerge in other brain regions. For instance, previous studies have shown HR animals had an increased DAT function in the NAcc and a decreased DAT function in cortex with no differences on striatum, suggesting a regionspecific role for DAT in mediating information transfer within the corticolimbic circuitry involved in response to novelty (Chefer et al, 2003, Zhu et al, 2007. Therefore, future work should extend the present findings by examining the impact of cocaine on other brain regions in HR and LR rats.…”
Section: Regulation Of Fadd By Cocaine M-j García-fuster Et Alsupporting
confidence: 53%
“…In particular, HR-LR differences in cocaine's impact on the FADD system may emerge in other brain regions. For instance, previous studies have shown HR animals had an increased DAT function in the NAcc and a decreased DAT function in cortex with no differences on striatum, suggesting a regionspecific role for DAT in mediating information transfer within the corticolimbic circuitry involved in response to novelty (Chefer et al, 2003, Zhu et al, 2007. Therefore, future work should extend the present findings by examining the impact of cocaine on other brain regions in HR and LR rats.…”
Section: Regulation Of Fadd By Cocaine M-j García-fuster Et Alsupporting
confidence: 53%
“…Several studies using inbred strains of mice have reported pharmacokinetic differences that could account for differential COC-induced locomotor activation Reith et al, 1987;Wiener and Reith, 1990;Jones et al, 1993). Others have found increased number and affinity of DATs in the NAc of high, compared to low, novelty responders (Chefer et al, 2003). However, we have demonstrated that these mechanisms are unlikely to explain the differential responsiveness of LCRs and HCRs to COC ; Table 1).…”
Section: Discussionmentioning
confidence: 49%
“…These individual differences have been observed both in outbred and inbred strains of mice (Ruth et al, 1988;George and Ritz, 1990;Henricks et al, 1997;Marley et al, 1998;Rocha et al, 1998). Likewise, variability in COC-induced behaviors has been observed in rats, predominantly in the propensity of rats, often initially classified as either low or high responders to novelty, to self-administer drug (Glick et al, 1994;Piazza et al, 2000), or to become behaviorally sensitized (Hooks et al, 1991a;Hooks et al, 1992;Djano and Martin-Iverson, 2000;Chefer et al, 2003). Differences in initial responsiveness of humans to cocaine also reflect both genetic and environmental influences and are one factor that determines whether or not an individual will become addicted to cocaine (Haertzen et al, 1983;Davidson et al, 1993).…”
Section: Introductionmentioning
confidence: 97%
“…Although controversy exists about the precise nature of this relationship (Carey et al 2003;Mitchell et al 2005), it is generally reported (e.g., Piazza et al 1989;Hooks et al 1991a;Klebaur et al 2001) that rats that are more reactive in a novel environment ("high responders") exhibit enhanced psychostimulant-induced behavioral sensitization and drug self-administration, compared to their less novelty-reactive counterparts ("low responders"). Neurobiological differences that have been associated with low and high responders to novelty include differences in dopamine (DA; Hooks et al 1991b;Marinelli and White 2000;Chefer et al 2003) and glucocorticoid systems (Piazza and LeMoal 1996;Kabbaj et al 2000).…”
Section: Introductionmentioning
confidence: 99%